PENERAPAN METODE VISUAL AUDITORY DALAM PENINGKATAN KEBERHASILAN TOILET TRAINING PADA ANAK PRASEKOLAH - Lilis Maghfuroh (UNUSA Press, 2017)
Toilet training or training for bowel and bladder is a major task in preschoolers. Since the percentage preschoolers who use diapres in RA Perwanida 3 Sukoanyar Turi, it proves that the children has not succeeded in toilet training. This study aims to determine the effect of visual auditory on toilet training in preschoolers. The design used